2020
DOI: 10.1039/d0cy00983k
|View full text |Cite
|
Sign up to set email alerts
|

Climbing the oxygen reduction reaction volcano plot with laser ablation synthesis of PtxY nanoalloys

Abstract: PtxY nanoparticles were synthesized by laser ablation in ethanol and proved to efficiently catalyze the oxygen reduction reaction in acid electrolyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Of great interest is the laser synthesis of nonequilibrium alloys with a tunable composition, [11] which enabled composition‐dependent investigations in electrocatalysis and nanomedicine. In electrocatalysis, alloys of Au, [12] Pt [13] and Pd [14] containing earth‐abundant elements like Fe and Y showed improved oxygen evolution or oxygen reduction performances, compared to the single element equivalents.…”
Section: What Is Your Current Research Focus and Why It Is Important?mentioning
confidence: 99%
“…Of great interest is the laser synthesis of nonequilibrium alloys with a tunable composition, [11] which enabled composition‐dependent investigations in electrocatalysis and nanomedicine. In electrocatalysis, alloys of Au, [12] Pt [13] and Pd [14] containing earth‐abundant elements like Fe and Y showed improved oxygen evolution or oxygen reduction performances, compared to the single element equivalents.…”
Section: What Is Your Current Research Focus and Why It Is Important?mentioning
confidence: 99%
“…In the past decade, many efforts have been devoted to synthesize Pt-RE alloy catalysts by a variety of methods, however, only a few researches have been proved to obtain Pt-RE alloys in a strict reduction environment. 29,30,32 Schwämmlein et al prepared Pt x Y/C alloy via thermally reducing YCl 3 with commercial Pt/C catalyst under the atmosphere of highly puri-ed H 2 at 1200 C. 33 Kanady et al synthesized Pt 3 Y nanoalloy particles by heating the mixture of alkali metal triethylborohydrides (MEt 3 BH, M ¼ K, Na), PtCl 4 and YCl 3 to 200 C in which MEt 3 BH was used as the reducing agent. 34 Itahara et al prepared Pt 5 Ce nanoparticles by using sodium vapor as the reducing agent at 600 C. 32 Recently, Kobayashi et al 35 reported the Pt 2 Y nanopowders with a reckoned particle size of 147.8 nm by molten salt synthesis (MSS), via mixing Pt with Y 2 O 3 in a molten LiCl-CaH 2 system under Ar atmosphere at 600 C, in which CaH 2 was used as the reducing agent.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the economic and technological problems related to the production, transport, and storage of hydrogen, the main FCs problem is on a different aspect: the high cost due to the low kinetic of the cathode reaction, the oxygen reduction reaction (ORR), and thus, the usage of Pt-based materials as catalysts is still required. 7 9 With their low cost, high availability, and good tolerance to poisoning, non-precious-metal catalysts (non-PGM) are the best known alternative to Pt. 10 12 During past decades, various non-PGM catalysts were investigated: M–N–C based on M–N x sites, non-precious-metal oxide, chalcogenides, and oxynitrides.…”
Section: Introductionmentioning
confidence: 99%